Theory Semigroups_Big
section ‹Big Sum over Finite Sets in Abelian Semigroups›
theory Semigroups_Big
imports Main
begin
text ‹
This theory is based on Isabelle/HOL's ‹Groups_Big.thy› written by T. Nipkow, L. C. Paulson, M. Wenzel and J. Avigad.
We have generalised a selection of its results from Abelian monoids to Abelian semigroups with an element that is a unit on the image of the semigroup operation.
›
subsection ‹Generic Abelian semigroup operation over a set›
locale abel_semigroup_set = abel_semigroup +
fixes z :: 'a (‹❙1›)
assumes z_neutral [simp]: "x ❙* y ❙* ❙1 = x ❙* y"
assumes z_idem [simp]: "❙1 ❙* ❙1 = ❙1"
begin
interpretation comp_fun_commute f
by standard (simp add: fun_eq_iff left_commute)
interpretation comp?: comp_fun_commute "f ∘ g"
by (fact comp_comp_fun_commute)
definition F :: "('b ⇒ 'a) ⇒ 'b set ⇒ 'a"
where eq_fold: "F g A = Finite_Set.fold (f ∘ g) ❙1 A"
lemma infinite [simp]: "¬ finite A ⟹ F g A = ❙1"
by (simp add: eq_fold)
lemma empty [simp]: "F g {} = ❙1"
by (simp add: eq_fold)
lemma insert [simp]: "finite A ⟹ x ∉ A ⟹ F g (insert x A) = g x ❙* F g A"
by (simp add: eq_fold)
lemma remove:
assumes "finite A" and "x ∈ A"
shows "F g A = g x ❙* F g (A - {x})"
proof -
from ‹x ∈ A› obtain B where B: "A = insert x B" and "x ∉ B"
by (auto dest: mk_disjoint_insert)
moreover from ‹finite A› B have "finite B" by simp
ultimately show ?thesis by simp
qed
lemma insert_remove: "finite A ⟹ F g (insert x A) = g x ❙* F g (A - {x})"
by (cases "x ∈ A") (simp_all add: remove insert_absorb)
lemma insert_if: "finite A ⟹ F g (insert x A) = (if x ∈ A then F g A else g x ❙* F g A)"
by (cases "x ∈ A") (simp_all add: insert_absorb)
lemma neutral: "∀x∈A. g x = ❙1 ⟹ F g A = ❙1"
by (induct A rule: infinite_finite_induct) simp_all
lemma neutral_const [simp]: "F (λ_. ❙1) A = ❙1"
by (simp add: neutral)
lemma F_one [simp]: "F g A ❙* ❙1 = F g A"
proof -
have "⋀f b B. F f (insert (b::'b) B) ❙* ❙1 = F f (insert b B) ∨ infinite B"
using insert_remove by fastforce
then show ?thesis
by (metis (no_types) all_not_in_conv empty z_idem infinite insert_if)
qed
lemma one_F [simp]: "❙1 ❙* F g A = F g A"
using F_one commute by auto
lemma F_g_one [simp]: "F (λx . g x ❙* ❙1) A = F g A"
apply (induct A rule: infinite_finite_induct)
apply simp
apply simp
by (metis one_F assoc insert)
lemma union_inter:
assumes "finite A" and "finite B"
shows "F g (A ∪ B) ❙* F g (A ∩ B) = F g A ❙* F g B"
using assms
proof (induct A)
case empty
then show ?case by simp
next
case (insert x A)
then show ?case
by (auto simp: insert_absorb Int_insert_left commute [of _ "g x"] assoc left_commute)
qed
corollary union_inter_neutral:
assumes "finite A" and "finite B"
and "∀x ∈ A ∩ B. g x = ❙1"
shows "F g (A ∪ B) = F g A ❙* F g B"
using assms by (simp add: union_inter [symmetric] neutral)
corollary union_disjoint:
assumes "finite A" and "finite B"
assumes "A ∩ B = {}"
shows "F g (A ∪ B) = F g A ❙* F g B"
using assms by (simp add: union_inter_neutral)
lemma union_diff2:
assumes "finite A" and "finite B"
shows "F g (A ∪ B) = F g (A - B) ❙* F g (B - A) ❙* F g (A ∩ B)"
proof -
have "A ∪ B = A - B ∪ (B - A) ∪ A ∩ B"
by auto
with assms show ?thesis
by simp (subst union_disjoint, auto)+
qed
lemma subset_diff:
assumes "B ⊆ A" and "finite A"
shows "F g A = F g (A - B) ❙* F g B"
proof -
from assms have "finite (A - B)" by auto
moreover from assms have "finite B" by (rule finite_subset)
moreover from assms have "(A - B) ∩ B = {}" by auto
ultimately have "F g (A - B ∪ B) = F g (A - B) ❙* F g B" by (rule union_disjoint)
moreover from assms have "A ∪ B = A" by auto
ultimately show ?thesis by simp
qed
lemma setdiff_irrelevant:
assumes "finite A"
shows "F g (A - {x. g x = z}) = F g A"
using assms by (induct A) (simp_all add: insert_Diff_if)
lemma not_neutral_contains_not_neutral:
assumes "F g A ≠ ❙1"
obtains a where "a ∈ A" and "g a ≠ ❙1"
proof -
from assms have "∃a∈A. g a ≠ ❙1"
proof (induct A rule: infinite_finite_induct)
case infinite
then show ?case by simp
next
case empty
then show ?case by simp
next
case (insert a A)
then show ?case by fastforce
qed
with that show thesis by blast
qed
lemma reindex:
assumes "inj_on h A"
shows "F g (h ` A) = F (g ∘ h) A"
proof (cases "finite A")
case True
with assms show ?thesis
by (simp add: eq_fold fold_image comp_assoc)
next
case False
with assms have "¬ finite (h ` A)" by (blast dest: finite_imageD)
with False show ?thesis by simp
qed
lemma cong [fundef_cong]:
assumes "A = B"
assumes g_h: "⋀x. x ∈ B ⟹ g x = h x"
shows "F g A = F h B"
using g_h unfolding ‹A = B›
by (induct B rule: infinite_finite_induct) auto
lemma strong_cong [cong]:
assumes "A = B" "⋀x. x ∈ B =simp=> g x = h x"
shows "F (λx. g x) A = F (λx. h x) B"
by (rule cong) (use assms in ‹simp_all add: simp_implies_def›)
lemma reindex_cong:
assumes "inj_on l B"
assumes "A = l ` B"
assumes "⋀x. x ∈ B ⟹ g (l x) = h x"
shows "F g A = F h B"
using assms by (simp add: reindex)
lemma UNION_disjoint:
assumes "finite I" and "∀i∈I. finite (A i)"
and "∀i∈I. ∀j∈I. i ≠ j ⟶ A i ∩ A j = {}"
shows "F g (⋃(A ` I)) = F (λx. F g (A x)) I"
apply (insert assms)
apply (induct rule: finite_induct)
apply simp
apply atomize
apply (subgoal_tac "∀i∈Fa. x ≠ i")
prefer 2 apply blast
apply (subgoal_tac "A x ∩ ⋃(A ` Fa) = {}")
prefer 2 apply blast
apply (simp add: union_disjoint)
done
lemma Union_disjoint:
assumes "∀A∈C. finite A" "∀A∈C. ∀B∈C. A ≠ B ⟶ A ∩ B = {}"
shows "F g (⋃C) = (F ∘ F) g C"
proof (cases "finite C")
case True
from UNION_disjoint [OF this assms] show ?thesis by simp
next
case False
then show ?thesis by (auto dest: finite_UnionD intro: infinite)
qed
lemma distrib: "F (λx. g x ❙* h x) A = F g A ❙* F h A"
by (induct A rule: infinite_finite_induct) (simp_all add: assoc commute left_commute)
lemma Sigma:
"finite A ⟹ ∀x∈A. finite (B x) ⟹ F (λx. F (g x) (B x)) A = F (case_prod g) (SIGMA x:A. B x)"
apply (subst Sigma_def)
apply (subst UNION_disjoint)
apply assumption
apply simp
apply blast
apply (rule cong)
apply rule
apply (simp add: fun_eq_iff)
apply (subst UNION_disjoint)
apply simp
apply simp
apply blast
apply (simp add: comp_def)
done
lemma related:
assumes Re: "R ❙1 ❙1"
and Rop: "∀x1 y1 x2 y2. R x1 x2 ∧ R y1 y2 ⟶ R (x1 ❙* y1) (x2 ❙* y2)"
and fin: "finite S"
and R_h_g: "∀x∈S. R (h x) (g x)"
shows "R (F h S) (F g S)"
using fin by (rule finite_subset_induct) (use assms in auto)
lemma mono_neutral_cong_left:
assumes "finite T"
and "S ⊆ T"
and "∀i ∈ T - S. h i = ❙1"
and "⋀x. x ∈ S ⟹ g x = h x"
shows "F g S = F h T"
proof-
have eq: "T = S ∪ (T - S)" using ‹S ⊆ T› by blast
have d: "S ∩ (T - S) = {}" using ‹S ⊆ T› by blast
from ‹finite T› ‹S ⊆ T› have f: "finite S" "finite (T - S)"
by (auto intro: finite_subset)
show ?thesis using assms(4)
by (simp add: union_disjoint [OF f d, unfolded eq [symmetric]] neutral [OF assms(3)])
qed
lemma mono_neutral_cong_right:
"finite T ⟹ S ⊆ T ⟹ ∀i ∈ T - S. g i = ❙1 ⟹ (⋀x. x ∈ S ⟹ g x = h x) ⟹
F g T = F h S"
by (auto intro!: mono_neutral_cong_left [symmetric])
lemma mono_neutral_left: "finite T ⟹ S ⊆ T ⟹ ∀i ∈ T - S. g i = ❙1 ⟹ F g S = F g T"
by (blast intro: mono_neutral_cong_left)
lemma mono_neutral_right: "finite T ⟹ S ⊆ T ⟹ ∀i ∈ T - S. g i = ❙1 ⟹ F g T = F g S"
by (blast intro!: mono_neutral_left [symmetric])
lemma mono_neutral_cong:
assumes [simp]: "finite T" "finite S"
and *: "⋀i. i ∈ T - S ⟹ h i = ❙1" "⋀i. i ∈ S - T ⟹ g i = ❙1"
and gh: "⋀x. x ∈ S ∩ T ⟹ g x = h x"
shows "F g S = F h T"
proof-
have "F g S = F g (S ∩ T)"
by(rule mono_neutral_right)(auto intro: *)
also have "… = F h (S ∩ T)" using refl gh by(rule cong)
also have "… = F h T"
by(rule mono_neutral_left)(auto intro: *)
finally show ?thesis .
qed
lemma reindex_bij_betw: "bij_betw h S T ⟹ F (λx. g (h x)) S = F g T"
by (auto simp: bij_betw_def reindex)
lemma reindex_bij_witness:
assumes witness:
"⋀a. a ∈ S ⟹ i (j a) = a"
"⋀a. a ∈ S ⟹ j a ∈ T"
"⋀b. b ∈ T ⟹ j (i b) = b"
"⋀b. b ∈ T ⟹ i b ∈ S"
assumes eq:
"⋀a. a ∈ S ⟹ h (j a) = g a"
shows "F g S = F h T"
proof -
have "bij_betw j S T"
using bij_betw_byWitness[where A=S and f=j and f'=i and A'=T] witness by auto
moreover have "F g S = F (λx. h (j x)) S"
by (intro cong) (auto simp: eq)
ultimately show ?thesis
by (simp add: reindex_bij_betw)
qed
lemma reindex_bij_betw_not_neutral:
assumes fin: "finite S'" "finite T'"
assumes bij: "bij_betw h (S - S') (T - T')"
assumes nn:
"⋀a. a ∈ S' ⟹ g (h a) = z"
"⋀b. b ∈ T' ⟹ g b = z"
shows "F (λx. g (h x)) S = F g T"
proof -
have [simp]: "finite S ⟷ finite T"
using bij_betw_finite[OF bij] fin by auto
show ?thesis
proof (cases "finite S")
case True
with nn have "F (λx. g (h x)) S = F (λx. g (h x)) (S - S')"
by (intro mono_neutral_cong_right) auto
also have "… = F g (T - T')"
using bij by (rule reindex_bij_betw)
also have "… = F g T"
using nn ‹finite S› by (intro mono_neutral_cong_left) auto
finally show ?thesis .
next
case False
then show ?thesis by simp
qed
qed
lemma reindex_nontrivial:
assumes "finite A"
and nz: "⋀x y. x ∈ A ⟹ y ∈ A ⟹ x ≠ y ⟹ h x = h y ⟹ g (h x) = ❙1"
shows "F g (h ` A) = F (g ∘ h) A"
proof (subst reindex_bij_betw_not_neutral [symmetric])
show "bij_betw h (A - {x ∈ A. (g ∘ h) x = ❙1}) (h ` A - h ` {x ∈ A. (g ∘ h) x = ❙1})"
using nz by (auto intro!: inj_onI simp: bij_betw_def)
qed (use ‹finite A› in auto)
lemma reindex_bij_witness_not_neutral:
assumes fin: "finite S'" "finite T'"
assumes witness:
"⋀a. a ∈ S - S' ⟹ i (j a) = a"
"⋀a. a ∈ S - S' ⟹ j a ∈ T - T'"
"⋀b. b ∈ T - T' ⟹ j (i b) = b"
"⋀b. b ∈ T - T' ⟹ i b ∈ S - S'"
assumes nn:
"⋀a. a ∈ S' ⟹ g a = z"
"⋀b. b ∈ T' ⟹ h b = z"
assumes eq:
"⋀a. a ∈ S ⟹ h (j a) = g a"
shows "F g S = F h T"
proof -
have bij: "bij_betw j (S - (S' ∩ S)) (T - (T' ∩ T))"
using witness by (intro bij_betw_byWitness[where f'=i]) auto
have F_eq: "F g S = F (λx. h (j x)) S"
by (intro cong) (auto simp: eq)
show ?thesis
unfolding F_eq using fin nn eq
by (intro reindex_bij_betw_not_neutral[OF _ _ bij]) auto
qed
lemma delta_remove:
assumes fS: "finite S"
shows "F (λk. if k = a then b k else c k) S = (if a ∈ S then b a ❙* F c (S-{a}) else F c (S-{a}))"
proof -
let ?f = "(λk. if k = a then b k else c k)"
show ?thesis
proof (cases "a ∈ S")
case False
then have "∀k∈S. ?f k = c k" by simp
with False show ?thesis by simp
next
case True
let ?A = "S - {a}"
let ?B = "{a}"
from True have eq: "S = ?A ∪ ?B" by blast
have dj: "?A ∩ ?B = {}" by simp
from fS have fAB: "finite ?A" "finite ?B" by auto
have "F ?f S = F ?f ?A ❙* F ?f ?B"
using union_disjoint [OF fAB dj, of ?f, unfolded eq [symmetric]] by simp
with True show ?thesis
using abel_semigroup_set.remove abel_semigroup_set_axioms fS by fastforce
qed
qed
lemma delta [simp]:
assumes fS: "finite S"
shows "F (λk. if k = a then b k else ❙1) S = (if a ∈ S then b a ❙* ❙1 else ❙1)"
by (simp add: delta_remove [OF assms])
lemma delta' [simp]:
assumes fin: "finite S"
shows "F (λk. if a = k then b k else ❙1) S = (if a ∈ S then b a ❙* ❙1 else ❙1)"
using delta [OF fin, of a b, symmetric] by (auto intro: cong)
lemma If_cases:
fixes P :: "'b ⇒ bool" and g h :: "'b ⇒ 'a"
assumes fin: "finite A"
shows "F (λx. if P x then h x else g x) A = F h (A ∩ {x. P x}) ❙* F g (A ∩ - {x. P x})"
proof -
have a: "A = A ∩ {x. P x} ∪ A ∩ -{x. P x}" "(A ∩ {x. P x}) ∩ (A ∩ -{x. P x}) = {}"
by blast+
from fin have f: "finite (A ∩ {x. P x})" "finite (A ∩ -{x. P x})" by auto
let ?g = "λx. if P x then h x else g x"
from union_disjoint [OF f a(2), of ?g] a(1) show ?thesis
by (subst (1 2) cong) simp_all
qed
lemma cartesian_product: "F (λx. F (g x) B) A = F (case_prod g) (A × B)"
apply (rule sym)
apply (cases "finite A")
apply (cases "finite B")
apply (simp add: Sigma)
apply (cases "A = {}")
apply simp
apply simp
apply (auto intro: infinite dest: finite_cartesian_productD2)
apply (cases "B = {}")
apply (auto intro: infinite dest: finite_cartesian_productD1)
done
lemma inter_restrict:
assumes "finite A"
shows "F g (A ∩ B) = F (λx. if x ∈ B then g x else ❙1) A"
proof -
let ?g = "λx. if x ∈ A ∩ B then g x else ❙1"
have "∀i∈A - A ∩ B. (if i ∈ A ∩ B then g i else ❙1) = ❙1" by simp
moreover have "A ∩ B ⊆ A" by blast
ultimately have "F ?g (A ∩ B) = F ?g A"
using ‹finite A› by (intro mono_neutral_left) auto
then show ?thesis by simp
qed
lemma inter_filter:
"finite A ⟹ F g {x ∈ A. P x} = F (λx. if P x then g x else ❙1) A"
by (simp add: inter_restrict [symmetric, of A "{x. P x}" g, simplified mem_Collect_eq] Int_def)
lemma Union_comp:
assumes "∀A ∈ B. finite A"
and "⋀A1 A2 x. A1 ∈ B ⟹ A2 ∈ B ⟹ A1 ≠ A2 ⟹ x ∈ A1 ⟹ x ∈ A2 ⟹ g x = ❙1"
shows "F g (⋃B) = (F ∘ F) g B"
using assms
proof (induct B rule: infinite_finite_induct)
case (infinite A)
then have "¬ finite (⋃A)" by (blast dest: finite_UnionD)
with infinite show ?case by simp
next
case empty
then show ?case by simp
next
case (insert A B)
then have "finite A" "finite B" "finite (⋃B)" "A ∉ B"
and "∀x∈A ∩ ⋃B. g x = ❙1"
and H: "F g (⋃B) = (F ∘ F) g B" by auto
then have "F g (A ∪ ⋃B) = F g A ❙* F g (⋃B)"
by (simp add: union_inter_neutral)
with ‹finite B› ‹A ∉ B› show ?case
by (simp add: H)
qed
lemma swap: "F (λi. F (g i) B) A = F (λj. F (λi. g i j) A) B"
unfolding cartesian_product
by (rule reindex_bij_witness [where i = "λ(i, j). (j, i)" and j = "λ(i, j). (j, i)"]) auto
lemma swap_restrict:
"finite A ⟹ finite B ⟹
F (λx. F (g x) {y. y ∈ B ∧ R x y}) A = F (λy. F (λx. g x y) {x. x ∈ A ∧ R x y}) B"
by (simp add: inter_filter) (rule swap)
lemma Plus:
fixes A :: "'b set" and B :: "'c set"
assumes fin: "finite A" "finite B"
shows "F g (A <+> B) = F (g ∘ Inl) A ❙* F (g ∘ Inr) B"
proof -
have "A <+> B = Inl ` A ∪ Inr ` B" by auto
moreover from fin have "finite (Inl ` A)" "finite (Inr ` B)" by auto
moreover have "Inl ` A ∩ Inr ` B = {}" by auto
moreover have "inj_on Inl A" "inj_on Inr B" by (auto intro: inj_onI)
ultimately show ?thesis
using fin by (simp add: union_disjoint reindex)
qed
lemma same_carrier:
assumes "finite C"
assumes subset: "A ⊆ C" "B ⊆ C"
assumes trivial: "⋀a. a ∈ C - A ⟹ g a = ❙1" "⋀b. b ∈ C - B ⟹ h b = ❙1"
shows "F g A = F h B ⟷ F g C = F h C"
proof -
have "finite A" and "finite B" and "finite (C - A)" and "finite (C - B)"
using ‹finite C› subset by (auto elim: finite_subset)
from subset have [simp]: "A - (C - A) = A" by auto
from subset have [simp]: "B - (C - B) = B" by auto
from subset have "C = A ∪ (C - A)" by auto
then have "F g C = F g (A ∪ (C - A))" by simp
also have "… = F g (A - (C - A)) ❙* F g (C - A - A) ❙* F g (A ∩ (C - A))"
using ‹finite A› ‹finite (C - A)› by (simp only: union_diff2)
finally have *: "F g C = F g A" using trivial by simp
from subset have "C = B ∪ (C - B)" by auto
then have "F h C = F h (B ∪ (C - B))" by simp
also have "… = F h (B - (C - B)) ❙* F h (C - B - B) ❙* F h (B ∩ (C - B))"
using ‹finite B› ‹finite (C - B)› by (simp only: union_diff2)
finally have "F h C = F h B"
using trivial by simp
with * show ?thesis by simp
qed
lemma same_carrierI:
assumes "finite C"
assumes subset: "A ⊆ C" "B ⊆ C"
assumes trivial: "⋀a. a ∈ C - A ⟹ g a = ❙1" "⋀b. b ∈ C - B ⟹ h b = ❙1"
assumes "F g C = F h C"
shows "F g A = F h B"
using assms same_carrier [of C A B] by simp
end
subsection ‹Generalized summation over a set›
text ‹Instead of @{term"∑x∈{x. P}. e"} we introduce the shorter ‹∑x|P. e›.›
no_notation Sum (‹∑›)
class ab_semigroup_add_0 = zero + ab_semigroup_add +
assumes zero_neutral [simp]: "x + y + 0 = x + y"
assumes zero_idem [simp]: "0 + 0 = 0"
begin
sublocale sum_0: abel_semigroup_set plus 0
defines sum_0 = sum_0.F
by unfold_locales simp_all
abbreviation Sum_0 (‹∑›)
where "∑ ≡ sum_0 (λx. x)"
end
context comm_monoid_add
begin
subclass ab_semigroup_add_0
by unfold_locales simp_all
end
text ‹Now: lots of fancy syntax. First, @{term "sum_0 (λx. e) A"} is written ‹∑x∈A. e›.›
no_syntax (ASCII)
"_sum" :: "pttrn ⇒ 'a set ⇒ 'b ⇒ 'b::comm_monoid_add" (‹(‹indent=3 notation=‹binder SUM››SUM (_/:_)./ _)› [0, 51, 10] 10)
no_syntax
"_sum" :: "pttrn ⇒ 'a set ⇒ 'b ⇒ 'b::comm_monoid_add" (‹(‹indent=2 notation=‹binder ∑››∑(_/∈_)./ _)› [0, 51, 10] 10)
syntax (ASCII)
"_sum0" :: "pttrn ⇒ 'a set ⇒ 'b ⇒ 'b::comm_monoid_add" (‹(‹indent=3 notation=‹binder SUM››SUM (_/:_)./ _)› [0, 51, 10] 10)
syntax
"_sum0" :: "pttrn ⇒ 'a set ⇒ 'b ⇒ 'b::comm_monoid_add" (‹(‹indent=2 notation=‹binder ∑››∑(_/∈_)./ _)› [0, 51, 10] 10)
syntax_consts
"_sum0" ⇌ sum_0
translations
"∑i∈A. b" ⇌ "CONST sum_0 (λi. b) A"
text ‹Instead of @{term"∑x∈{x. P}. e"} we introduce the shorter ‹∑x|P. e›.›
no_syntax (ASCII)
"_qsum" :: "pttrn ⇒ bool ⇒ 'a ⇒ 'a" (‹(‹indent=3 notation=‹binder SUM Collect››SUM _ |/ _./ _)› [0, 0, 10] 10)
no_syntax
"_qsum" :: "pttrn ⇒ bool ⇒ 'a ⇒ 'a" (‹(‹indent=2 notation=‹binder ∑ Collect››∑_ | (_)./ _)› [0, 0, 10] 10)
syntax (ASCII)
"_qsum0" :: "pttrn ⇒ bool ⇒ 'a ⇒ 'a" (‹(‹indent=3 notation=‹binder SUM Collect››SUM _ |/ _./ _)› [0, 0, 10] 10)
syntax
"_qsum0" :: "pttrn ⇒ bool ⇒ 'a ⇒ 'a" (‹(‹indent=2 notation=‹binder ∑ Collect››∑_ | (_)./ _)› [0, 0, 10] 10)
syntax_consts
"_qsum0" ⇌ sum_0
translations
"∑x|P. t" => "CONST sum_0 (λx. t) {x. P}"
print_translation ‹
[(\<^const_syntax>‹sum_0›, K (Collect_binder_tr' \<^syntax_const>‹_qsum›))]
›
lemma (in ab_semigroup_add_0) sum_image_gen_0:
assumes fin: "finite S"
shows "sum_0 g S = sum_0 (λy. sum_0 g {x. x ∈ S ∧ f x = y}) (f ` S)"
proof -
have "{y. y∈ f`S ∧ f x = y} = {f x}" if "x ∈ S" for x
using that by auto
then have "sum_0 g S = sum_0 (λx. sum_0 (λy. g x) {y. y∈ f`S ∧ f x = y}) S"
by simp
also have "… = sum_0 (λy. sum_0 g {x. x ∈ S ∧ f x = y}) (f ` S)"
by (rule sum_0.swap_restrict [OF fin finite_imageI [OF fin]])
finally show ?thesis .
qed
subsubsection ‹Properties in more restricted classes of structures›
lemma sum_Un2:
assumes "finite (A ∪ B)"
shows "sum_0 f (A ∪ B) = sum_0 f (A - B) + sum_0 f (B - A) + sum_0 f (A ∩ B)"
proof -
have "A ∪ B = A - B ∪ (B - A) ∪ A ∩ B"
by auto
with assms show ?thesis
by simp (subst sum_0.union_disjoint, auto)+
qed
class ordered_ab_semigroup_add_0 = ab_semigroup_add_0 + ordered_ab_semigroup_add
begin
lemma add_nonneg_nonneg [simp]: "0 ≤ a ⟹ 0 ≤ b ⟹ 0 ≤ a + b"
using add_mono[of 0 a 0 b] by simp
lemma add_nonpos_nonpos: "a ≤ 0 ⟹ b ≤ 0 ⟹ a + b ≤ 0"
using add_mono[of a 0 b 0] by simp
end
lemma (in ordered_ab_semigroup_add_0) sum_mono:
"(⋀i. i∈K ⟹ f i ≤ g i) ⟹ (∑i∈K. f i) ≤ (∑i∈K. g i)"
by (induct K rule: infinite_finite_induct) (use add_mono in auto)
lemma (in ordered_ab_semigroup_add_0) sum_mono_00:
"(⋀i. i∈K ⟹ f i + 0 ≤ g i + 0) ⟹ (∑i∈K. f i) ≤ (∑i∈K. g i)"
proof (induct K rule: infinite_finite_induct)
case (infinite A)
then show ?case by simp
next
case empty
then show ?case by simp
next
case (insert x F)
then show ?case
proof -
fix x :: 'b and F :: "'b set"
assume a1: "finite F"
assume a2: "x ∉ F"
assume a3: "(⋀i. i ∈ F ⟹ f i + 0 ≤ g i + 0) ⟹ sum_0 f F ≤ sum_0 g F"
assume a4: "⋀i. i ∈ insert x F ⟹ f i + 0 ≤ g i + 0"
obtain bb :: 'b where
f5: "bb ∈ F ∧ ¬ f bb + 0 ≤ g bb + 0 ∨ sum_0 f F ≤ sum_0 g F"
using a3 by blast
have "∀b. x ≠ b ∨ f b + 0 ≤ g b + 0"
using a4 by simp
then have "∀a aa. f x + 0 + a ≤ g x + 0 + aa ∨ ¬ a ≤ aa"
using add_mono by blast
then show "sum_0 f (insert x F) ≤ sum_0 g (insert x F)"
using f5 a4 a2 a1 by (metis (no_types) add_assoc insert_iff sum_0.insert sum_0.one_F)
qed
qed
lemma (in ordered_ab_semigroup_add_0) sum_mono_0:
"(⋀i. i∈K ⟹ f i + 0 ≤ g i) ⟹ (∑i∈K. f i) ≤ (∑i∈K. g i)"
apply (rule sum_mono_00)
by (metis add_right_mono zero_neutral)
context ordered_ab_semigroup_add_0
begin
lemma sum_nonneg: "(⋀x. x ∈ A ⟹ 0 ≤ f x) ⟹ 0 ≤ sum_0 f A"
proof (induct A rule: infinite_finite_induct)
case infinite
then show ?case by simp
next
case empty
then show ?case by simp
next
case (insert x F)
then have "0 + 0 ≤ f x + sum_0 f F" by (blast intro: add_mono)
with insert show ?case by simp
qed
lemma sum_nonpos: "(⋀x. x ∈ A ⟹ f x ≤ 0) ⟹ sum_0 f A ≤ 0"
proof (induct A rule: infinite_finite_induct)
case infinite
then show ?case by simp
next
case empty
then show ?case by simp
next
case (insert x F)
then have "f x + sum_0 f F ≤ 0 + 0" by (blast intro: add_mono)
with insert show ?case by simp
qed
lemma sum_mono2:
assumes fin: "finite B"
and sub: "A ⊆ B"
and nn: "⋀b. b ∈ B-A ⟹ 0 ≤ f b"
shows "sum_0 f A ≤ sum_0 f B"
proof -
have "sum_0 f A ≤ sum_0 f A + sum_0 f (B-A)"
by (metis add_left_mono sum_0.F_one nn sum_nonneg)
also from fin finite_subset[OF sub fin] have "… = sum_0 f (A ∪ (B-A))"
by (simp add: sum_0.union_disjoint del: Un_Diff_cancel)
also from sub have "A ∪ (B-A) = B" by blast
finally show ?thesis .
qed
lemma sum_le_included:
assumes "finite s" "finite t"
and "∀y∈t. 0 ≤ g y" "(∀x∈s. ∃y∈t. i y = x ∧ f x ≤ g y)"
shows "sum_0 f s ≤ sum_0 g t"
proof -
have "sum_0 f s ≤ sum_0 (λy. sum_0 g {x. x∈t ∧ i x = y}) s"
proof (rule sum_mono_0)
fix y
assume "y ∈ s"
with assms obtain z where z: "z ∈ t" "y = i z" "f y ≤ g z" by auto
hence "f y + 0 ≤ sum_0 g {z}"
by (metis Diff_eq_empty_iff add_commute finite.simps add_left_mono sum_0.empty sum_0.insert_remove subset_insertI)
also have "... ≤ sum_0 g {x ∈ t. i x = y}"
apply (rule sum_mono2)
using assms z by simp_all
finally show "f y + 0 ≤ sum_0 g {x ∈ t. i x = y}" .
qed
also have "… ≤ sum_0 (λy. sum_0 g {x. x∈t ∧ i x = y}) (i ` t)"
using assms(2-4) by (auto intro!: sum_mono2 sum_nonneg)
also have "… ≤ sum_0 g t"
using assms by (auto simp: sum_image_gen_0[symmetric])
finally show ?thesis .
qed
end
lemma sum_comp_morphism:
"h 0 = 0 ⟹ (⋀x y. h (x + y) = h x + h y) ⟹ sum_0 (h ∘ g) A = h (sum_0 g A)"
by (induct A rule: infinite_finite_induct) simp_all
lemma sum_cong_Suc:
assumes "0 ∉ A" "⋀x. Suc x ∈ A ⟹ f (Suc x) = g (Suc x)"
shows "sum_0 f A = sum_0 g A"
proof (rule sum_0.cong)
fix x
assume "x ∈ A"
with assms(1) show "f x = g x"
by (cases x) (auto intro!: assms(2))
qed simp_all
end